Religiosity of baby-boomers in young adulthood: Associations with psychological well-being over the life course. (June 2022) - Hwang, Woosang; Cheng, Kent Jason; Brown, Maria T.; Silverstein, Merril
Abstract: Although several studies have discovered positive relationships between religion and various aspects of mental health, less is known about longitudinal associations between religiosity and psychological well-being over the life course. We examined how religious latent classes during the transition to adulthood are associated with trajectories of psychological well-being over 45 years. We selected 798 young-adults baby-boomers from the 1971 wave of the Longitudinal Study of Generation (mean age: 19 years) and tracked their psychological well-being over nine waves up to the 2016 wave (mean age: 64 years). Latent class analysis focused on four religiosity domains (religious service attendance, religious intensity, civic value of religion, literal beliefs) identified four distinct latent religious classes: strongly religious, weakly religious, liberally religious, and privately religious. Results of latent growth curve modeling showed that strongly religious baby-boomers during the transition to adulthood generally reported better psychological well-being than weakly religious baby-boomers at the same stage in life. In addition, psychological well-being in strongly, liberally, and privately religious baby-boomers followed a consistently upward trend across the life course, whereas among weakly religious baby-boomers psychological well-being followed an inverted u-curve (increased until mid-40s and decreased thereafter). Findings suggest that earlier religiosity may serve as a significant predictor affecting psychological well-being throughout the adult life course. Highlights: Identifying multidimensional categories of religiosity in young adulthood using a person-centered approach. Addressing how baby-boomers' religiosity classes in young adulthood were related to their psychological well-being. Understanding the long-term impact of religiosity over the life course.